Answer:
x + 1
y = 9
Step-by-step explanation:
In order to solve this question we need to represent "y "in terms of "x" in the first equation, and the plug in the "y" value in the first equation into the second one. Luckily for us in the first equation it already shows what "y" is equal to in terms of "x" (based on the first equation y = -x + 10). Now we just need to plug in the value that we got instead of "y" in the second equation, and so we get....
y = 7x + 2
(plug in the y value and get the following ….)
-x + 10 = 7x + 2
(now just solve the following equation)
-x + 10 + x = 7x + 2 + x
10 = 8x + 2
10 - 2 = 8x + 2 - 2
8 = 8x
8/8 = 8x/8
1 = x
Now that we know the value of "x", all we need to do now is substitute the value of "x" into any of the equations and we will get the value of "y". So we do the following.....
y = 7x + 2
y = 7(1) + 2
y = 7 + 2
y = 9
Answer:
x=21
Step-by-step explanation:
well, geez - just do the math!
3/7 * 49 = 21
SAS because you have 2 known side lengths and one angle!
Answer:Since -2 can not equal 0, there is no solution. The lines are parallel. It is an inconsistent system.
Step-by-step explanation:
The first step in solving a system of equations by substitution is solving one of the equations for one of the variables
x - y = 0 Equation 1
x - y + y = 0 +y Add y to each side
x = y Simplify
After solving an equation for one of the variables, substitute that value into the other equation. In this problem, I can substitute y for x.
x - y - 2 = 0 Equation 2
y - y - 2 = 0 Substitute the value of x from equation 1
0 - 2 = 0 Inverse Property of addition
-2 = 0 Identity Property of addition